Bangladesh Social Protection Public Expenditure Review - World Bank (World Bank, Dhaka, 2021)
Bangladesh’s economy is growing at a healthy pace and macro conditions are strong. Progress in social outcomes in Bangladesh is inspiring other countries, but deep challenges persist as the pace of poverty reduction slows down. Bangladesh labor market is dominated by low-productivity and informality. Urbanization also has important consequences for social protection spending and design. Bangladesh is ranked as the most vulnerable country in the world to climate related shocks. Social protection in Bangladesh has been evolving since the 1970s, through innovation and experimentation. The core issue in Bangladesh, more than the overall resources devoted to social protection, seems to be around how well these resources are deployed. This public expenditure review focuses on four aspects of quality of spending, which together point to elements that could be reformed to increase the overall impact of the resources devoted to this sector. The first key question is whether these important resources are allocated in a manner that focuses on the issues they are meant to address (discussed in Chapter 2). The second set of questions relate to whether the program themselves are designed to be impactful, that whether they are reaching the intended beneficiaries in a manner that’s adequate or commensurate with their needs (discussed in Chapter 3). A third set of issues relate to whether the processes used to prioritize, budget and finance these programs are efficient (discussed in chapter 4). Finally, the last elements essential to the overall effectiveness of the social protection expenditure is the efficiency in the delivery of the programs to their beneficiaries, from the central to the local level (discussed in chapter 5).